2016
DOI: 10.1161/strokeaha.116.013173
|View full text |Cite
|
Sign up to set email alerts
|

Female Sex, Time in Therapeutic Range, and Clinical Outcomes in Atrial Fibrillation Patients Taking Warfarin

Abstract: Background and Purpose-Female patients have higher risk for stroke than male patients in nonanticoagulated atrial fibrillation patients, but limited data are available on sex differences in stroke and bleeding outcomes among patients with anticoagulated atrial fibrillation on warfarin, especially in relation to quality of anticoagulation control, as reflected by the time in therapeutic range (TTR). Methods-We investigated adverse outcomes in females (n=791) and males (n=1501) Table). Cardiovascular death rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Because of the retrospective nature of our study and access only to INR results prior to enrolment at the clinic, we were unable to measure outcomes in terms of adverse events and influence of interacting medications. However, TTR has been shown to be a good surrogate marker of outcomes with warfarin therapy, and enrolment in the dedicated warfarin clinic was shown to improve TTR even after only a six‐month period. This is likely to translate into improved outcomes from warfarin therapy but further investigation is required to confirm this improvement in terms of clinical efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the retrospective nature of our study and access only to INR results prior to enrolment at the clinic, we were unable to measure outcomes in terms of adverse events and influence of interacting medications. However, TTR has been shown to be a good surrogate marker of outcomes with warfarin therapy, and enrolment in the dedicated warfarin clinic was shown to improve TTR even after only a six‐month period. This is likely to translate into improved outcomes from warfarin therapy but further investigation is required to confirm this improvement in terms of clinical efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…51 The low anticoagulant quality was correlated with the increase in risk of bleeding or thromboembolism. [52][53][54] Low TTR (<67%) was associated with the increase in D-dimer level. 55 Moreover, INR variation during the anticoagulation period (INR coefficient of variation, INR-CV%), which is another indicator of anticoagulation quality, was also a cause of the increase in D-dimer level.…”
Section: Use Of D-dimer To Evaluate Anticoagulation Qualitymentioning
confidence: 99%
“…There are several known risk factors for bleeding during treatment with oral anticoagulants, such as age, chronic comorbidities, prior bleeding and certain co-medications which are included in the HAS-BLED score [1]. Sex is not included in this risk score, and conflicting results have been found in different populations with several studies showing no difference in bleeding risk between the sexes [2][3][4][5][6][7], while other studies found a higher risk of bleeding in men [8][9][10][11]. To our knowledge, there is a lack of large population-based register studies on sex differences in severe bleeding risks in warfarin-treated patients.…”
Section: Introductionmentioning
confidence: 99%